TRAGEDY OF KANJURUHAN STADIUM SEEN FROM PERSPECTIVE OF HUMAN RIGHTS - Naufal Aditya Nugraha; Moh Rio Ferdihansyah R. H. A; M.Asif Nur Fauzi C (JURNAL SETIA PANCASILA, 2023)
The Kanjuruhan Stadium incident involves a conflict between football supporters and law enforcement, resulting in various violations of human rights. This research aims to understand the implications of the event on human rights and highlight the issues that arise in the context of security and law enforcement. The study utilizes a descriptive-analytical approach by analyzing various sources of information, including media reports, official documents, and statistical data related to the Kanjuruhan Stadium incident. Firstly, this paper identifies the human rights violations that occurred during the event, such as excessive use of violence and arbitrary arrests. The findings of this research indicate serious violations of human rights during the Kanjuruhan Stadium incident, which contravene the fundamental principles of human rights, including the right to security and protection from inhumane treatment. This paper contributes to the understanding of the importance ofupholding human rights in the context of sporting events. The research provides policy recommendations for the government, law enforcement, and other relevant parties to ensure better protection of human rights inmanaging similar situations in the future. Similarly, this study encourages the public to enhance awareness of the importance of respecting human rights and participating in promoting human rights principles in the context of sports.